1999
DOI: 10.1117/12.373561
|View full text |Cite
|
Sign up to set email alerts
|

<title>Compressed-domain video parsing using energy histograms of the lower-frequency DCT coefficients</title>

Abstract: As an increasing amount of audio-visual data is stored, distributed, and used in the compressed form, compressed-domain techniques will be favorable. However, as conventional features may not be directly accessible in the compressed domain, exploration of new compressed domain features will become mandatory. Studies have shown that the DC coefficients of a DCT-compressed video can be used to detect shot transitions for relatively simple video sequences. In this work, the use of the energy histogram of the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In particular, research has shown that the DC coefficients can be used to detect shot transitions in MPDG [184]. Previous work using Motion-JPEG indicated that AC coefficients could be used to detect scene changes [185]. This section presents a new method called Twin-Window Amplification Method (TWAM) [181,182] for detecting scene changes.…”
Section: Video Parsing In Compressed Domainmentioning
confidence: 99%
“…In particular, research has shown that the DC coefficients can be used to detect shot transitions in MPDG [184]. Previous work using Motion-JPEG indicated that AC coefficients could be used to detect scene changes [185]. This section presents a new method called Twin-Window Amplification Method (TWAM) [181,182] for detecting scene changes.…”
Section: Video Parsing In Compressed Domainmentioning
confidence: 99%
“…Coefficients in the 8x8 DCT block can be classified into frequency bands that roughly correspond to smooth area, horizontal and vertical edges, and noisy areas [34]. Bao et al [35] use energy histogram of low frequency coefficients as the matching features for video frame similarity. This feature can been seen as a rough description of the global texture pattern in the video frame.…”
Section: Visual Feature Extractionmentioning
confidence: 99%